No Pathogen-Specific Sign or Symptom Predicts the Etiology of Monomicrobial Nongonococcal Urethritis in Men. Issue 5 (May 2020) - Jordan, Stephen J.; Toh, Evelyn; Williams, James A.; Fortenberry, Lora J.; LaPradd, Michelle; Ryan, John D.; Nelson, David E.; Batteiger, Teresa A.
Abstract : Abstract: Identifying pathogen-specific signs or symptoms of nongonococcal urethritis could improve syndromic management accuracy. We evaluated nongonococcal urethritis signs and symptoms in 220 men with single-pathogen infections ( Chlamydia trachomatis, Mycoplasma genitalium, Trichomonas vaginalis, or Ureaplasma urealyticum ) or idiopathic urethritis. No individual sign or symptom accurately predicted the infectious etiology. Abstract : We evaluated whether pathogen-specific signs and symptoms could inform pathogen-directed nongonococcal urethritis treatment in men. No sign or symptom reliably differentiated infection with any nongonococcal urethritis–associated pathogen. Pathogen-directed treatment will require point-of-care molecular tests.